Laterality: Coffee vs Tea - Is it forensically relevant? (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The question of laterality is discussed in this paper pertaining to use of the right or the left hand. Interestingly, some amazing cue is derived which though do not confirm to the projection, yet demonstrate conformity to deviant reasoning leading to promising forensic lead.
Keywords: Laterality; Left-hander; Right-hander; Forensic relevance